Allocentric coordinate spatial representations are impaired in aMCI and Alzheimer’s disease patients - Ruggiero, Gennaro; Ruotolo, Francesco; Iavarone, Alessandro; Iachini, Tina (Behavioural brain research, 2020)
•We test ego-/allo-centric and categorical/coordinate encodings in aMCI and AD patients.•How is the allocentric deficit of aMCI/AD linked to categorical/coordinate relations?•Subjects give right/left and distance based judgments combined with reference frames.•aMCI and AD groups show a selective allocentric-coordinate not categorical deficit.•-Conversion from normal aging to AD may be traced in allocentric distance-based deficits. Research has reported deficits in egocentric (subject-to-object) and mainly allocentric (object-to-object) spatial representations in the early stages of the Alzheimer’s disease (eAD). To identify early cognitive signs of neurodegenerative conversion, several studies have shown alterations in both reference frames, especially the allocentric ones in amnestic-Mild Cognitive Impairment (aMCI) and eAD patients. However, egocentric and allocentric spatial frames of reference are intrinsically connected with coordinate (metric/variant) and categorical (non-metric/invariant) spatial relations. This raises the question of whether allocentric deficit found to detect the conversion from aMCI to dementia is differently affected when combined with categorical or coordinate spatial relations. Here, we compared eAD and aMCI patients to Normal Controls (NC) on the Ego-Allo/Cat-Coor spatial memory task. Participants memorized triads of objects and then were asked to provide right/left (i.e. categorical) and distance based (i.e. coordinate) judgments according to an egocentric or allocentric reference frame. Results showed a selective deficit of coordinate, but not categorical, allocentric judgments in both aMCI and eAD patients as compared to NC group. These results suggest that a sign of the departure from normal/healthy aging towards the AD may be traced in elderly people’s inability to represent metric distances among elements in the space.